Does lethal control of top-predators release mesopredators? A re-evaluation of three Australian case studies - Allen, Benjamin L.; Lundie-Jenkins, Geoff; Burrows, Neil D.; Engeman, Richard M.; Fleming, Peter J.S.; Leung, Luke K.-P. (Ecological management & restoration, 2014)
Summary Top‐predators can sometimes be important for structuring fauna assemblages in terrestrial ecosystems. Through a complex trophic cascade, the lethal control of top‐predators has been predicted to elicit positive population responses from mesopredators that may in turn increase predation pressure on prey species of concern. In support of this hypothesis, many relevant research papers, opinion pieces and literature reviews identify three particular case studies as supporting evidence for top‐predator control‐induced release of mesopredators in Australia. However, many fundamental details essential for supporting this hypothesis are missing from these case studies, which were each designed to investigate alternative aims. Here, we re‐evaluate the strength of evidence for top‐predator control‐induced mesopredator release from these three studies after comprehensive analyses of associated unpublished correlative and experimental data. Circumstantial evidence alluded to mesopredator releases of either the European Red Fox (Vulpes vulpes) or feral Cat (Felis catus) coinciding with Dingo (Canis lupus dingo) control in each case. Importantly, however, substantial limitations in predator population sampling techniques and/or experimental designs preclude strong assertions about the effect of lethal control on mesopredator populations from these studies. In all cases, multiple confounding factors and plausible alternative explanations for observed changes in predator populations exist. In accord with several critical reviews and a growing body of demonstrated experimental evidence on the subject, we conclude that there is an absence of reliable evidence for top‐predator control‐induced mesopredator release from these three case studies. Well‐designed and executed studies are critical for investigating potential top‐predator control‐induced mesopredator release.